2016
DOI: 10.1016/s2215-0366(16)30284-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of maternal depression, risk factors, and child outcomes in low-income and middle-income countries

Abstract: Maternal depression, a non-psychotic depressive episode of mild to major severity, is one of the major contributors of pregnancy-related morbidity and mortality. Maternal depression (antepartum or post partum) has been linked to negative health-related behaviours and adverse outcomes, including psychological and developmental disturbances in infants, children, and adolescents. Despite its enormous burden, maternal depression in low-income and middle-income countries remains under-recognised and undertreated. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

53
778
8
40

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 837 publications
(879 citation statements)
references
References 174 publications
53
778
8
40
Order By: Relevance
“…Moreover, many of these measurements did not take place during a time frame that would yield a DSM or ICD (International Classification of Diseases) diagnosis (within four and six weeks after childbirth, respectively) (Underwood et al, 2016). Most recently, a review of perinatal depression in low and middle income countries by Gelaye et al (2016) found the prevalence of prenatal depression to be 25.8%, while the postnatal prevalence was 19.7%. This review is limited because of its exclusion of high income countries; additionally, although significant heterogeneity was detected between studies, no efforts were made to further investigate its sources.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many of these measurements did not take place during a time frame that would yield a DSM or ICD (International Classification of Diseases) diagnosis (within four and six weeks after childbirth, respectively) (Underwood et al, 2016). Most recently, a review of perinatal depression in low and middle income countries by Gelaye et al (2016) found the prevalence of prenatal depression to be 25.8%, while the postnatal prevalence was 19.7%. This review is limited because of its exclusion of high income countries; additionally, although significant heterogeneity was detected between studies, no efforts were made to further investigate its sources.…”
Section: Introductionmentioning
confidence: 99%
“…Nėščiųjų ir pagimdžiusiųjų motinų nepsichoziniai vidutinio sunkumo ir sunkūs depresijos epizodai daro didelę įtaką su nėštumu susijusiam sergamumui ir mirtingumui, tačiau mažas ir vidutines pajamas gaunančiose šalyse motinų depresijos diagnostika ir gydymas išlieka nepakankamas [1]. Diagnostikos bei gydymo sunkumų priežastis Lietuvos populiacijoje tyrusi ir aprašiusi V. Danilevičiūtė (2006) kartu atskleidė ir šios problemos kompleksiškumą -depresijos diagnostikos bei gydymo netikslumų ir klaidų priežastis suskirstydama į 3 pagrindines grupes: 1) pacienčių, 2) medikų (psichikos sveikatos ir bendrosios sveikatos priežiūros)…”
Section: įVadasunclassified
“…Pogimdyminė depresija nustatoma 19,2 % motinų. Apskritai pirmaisiais metais po gimdymo depresijos paplitimas svyruoja tarp 6,5% ir 12,9% [1]. Po-SVEIKATOS MOKSLAI / HEALTH SCIENCES IN EASTERN EUROPE ISSN 1392-6373 print / 2335-867X online 2017, 27 tomas, Nr.…”
Section: Pogimdyminių Depresinių Sutrikimų Ankstyvoji Diagnostika -Efunclassified
“…Employment is helpful to people with severe mental disorders and reduces costs of running mental health services in the long term. [2] Postpartum depression affects up to 20% of mothers, [3] with higher prevalence in low-income and middle-income countries than in high-income countries. Low socioeconomic status and low social support increase the risk of postpartum depression; [3] helping women return to work can therefore promote recovery and save long term service costs.…”
mentioning
confidence: 99%
“…[2] Postpartum depression affects up to 20% of mothers, [3] with higher prevalence in low-income and middle-income countries than in high-income countries. Low socioeconomic status and low social support increase the risk of postpartum depression; [3] helping women return to work can therefore promote recovery and save long term service costs. A 2014 analysis estimated that, in the UK, postpartum depression costs health and social care services £1688 per case.…”
mentioning
confidence: 99%